PENINGKATAN PARTISIPASI, KETERLIBATAN, DAN ETIKA MANAJEMEN DALAM PENGGUNAAN TEKNOLOGI INFORMASI PADA ORGANISASI PELAYANAN KEMANUSIAAN DI KABUPATEN BANYUMAS - Rini Widianingsih; Halomoan Ompusungu (Politeknik Kesejahteraan Sosial Bandung, 2015)
Abstract Development of an organization's information systems aspects of the use of information technology is complex and requires judgment ,management support and management etic as it relates to cost and benefit. It requires good management support through participation and involvement in the planning, organizing, realize, implement, and manage strategically. This study will examine the influence of perception management support through participation and involvement in the development of the use of information technology in the human service organization information systems. Data were collected through questionnaires responded to by the managers of human service organization in Banyumas. Impact analyzed using multiple linear regressions, along with tests of significance.Research results. Participation, involvement and etic of management (partially or simultaneously) influence (significant) towards the development of the use of information technology in the human service organization information systems.Suggestions: development of the use of information technology in the hunan service organization information systems can be done by increasing the participation and involvement of management through a clear segregation of functions, focus group discussions, and workshops about the development of information technology vision.Keywords: participation, Involvement, etic, management, information technology, information systemsAbstrakPengembangan sistem informasi aspek organisasi dari penggunaan teknologi informasi yang kompleks dan memerlukan pertimbangan, dukungan manajemen dan manajemen etik yang berkaitan dengan biaya dan manfaat. Hal ini membutuhkan dukungan manajemen yang baik melalui partisipasi dan keterlibatan dalam perencanaan, pengorganisasian, menyadari, melaksanakan, dan mengelola strategis. Penelitian ini akan mengkaji pengaruh dukungan manajemen persepsi melalui partisipasi dan keterlibatan dalam pengembangan penggunaan teknologi informasi dalam sistem informasi organisasi pelayanan kemanusiaan. Data dikumpulkan melalui kuesioner ditanggapi oleh manajer organisasi pelayanan kemanusiaan di Banyumas. Dampak dianalisis menggunakan regresi linear, bersama dengan uji signifikansi.Hasil penelitian. Partisipasi, keterlibatan dan etik manajemen (parsial maupun simultan) berpengaruh (signifikan) terhadap pengembangan penggunaan teknologi informasi dalam sistem informasi organisasi pelayanan kemanusiaan.Saran: pengembangan penggunaan teknologi informasi dalam sistem informasi lembaga pelayanan kemanusiaan dapat dilakukan dengan meningkatkan partisipasi dan keterlibatan manajemen melalui pemisahan yang jelas fungsi, diskusi kelompok terfokus, dan lokakarya tentang pengembangan visi teknologi informasi.Kata kunci: partisipasi, keterlibatan, etika, manajemen, teknologi informasi, sistem informasi